Differentiation dynamics of mammary epithelial cells revealed by single-cell RNA sequencing - Karsten Bach (Nature Portfolio, 2017)
There is a need to understand how mammary epithelial cells respond to changes at various developmental stages. Here, the authors use single-cell RNA sequencing of mammary epithelial cells at different adult developmental stages, identifying different cell types and charting their developmental trajectory.